Syi’ru Al-Jazal Al-Magribiy f ī Ḍaw’ Ad-Dirāsat At-Taqābuliyyah Baina Al ‘Arabiyyah Al-Fusha wa Al-‘Āmiyyat Al-Magribiyyah - Sita Yulia Agustina; Wildana Wargadinata; Faris Maturedy; Iffat Maimunah (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract This study aims to determine the difference between Fusha and Amiyah languages in Omar Benhidi's syiir Zajal by using contrastive analysis on two aspects of language, namely phonological and morphological aspects. This research is a qualitative descriptive study. The primary sources of data used in the study are three poetries of Omar Benhidi's on his YouTube channel entitled as-Shahaab, as-Siiruur and Baaridul Kattaf. The data collection techniques were listening technique, proficient involvement, and note-taking technique. The data analysis technique adopted the Miles & Huberman model which consists of reduction, display, and conclusion. The results of this research are: 1) From the morphonological aspect, the word comparison from Darijah Maghribiyah to Fusha include the differences in 21 words. Those are in the form of combining Dhamir Mutakallim Wahdah with Dhomir Mutakallim Ma’al Ghair, then summarizing Shigat Isim Maushul, Naht, replacing Dhamir Ha with Wawu letter, adding of Kaf letters at the beginning of Fi'il Mudhari', and Isim Mudzakkar which applies on Muannats. 2) From the phonological aspect, the results cover the differences in 30 words; namely in the form of a sound change, shortened sound, and the Ibdal. Keywords: Amiyah, Morphology, Phonology, Syiir, Zajal al-Maghriby